Stoma reversal after intended restorative rectal cancer resection in Denmark: nationwide population-based study. Issue 6 (6th October 2020) - Jørgensen, J B; Erichsen, R; Pedersen, B G; Laurberg, S; Iversen, L H
Abstract: Background: Data on stoma reversal following restorative rectal resection (RRR) with a diverting stoma are conflicting. This study investigated a Danish population-based cohort of patients undergoing RRR to evaluate factors predictive of stoma reversal during 3 years of follow-up. Methods: Patients from national registries with rectal cancer undergoing RRR or Hartmann's procedure with curative intent between May 2001 and April 2012 were included. Patients with a diverting stoma were followed from the time of primary rectal cancer resection to date of stoma reversal, death, emigration, or end of 3-year follow-up. The cumulative incidence proportion (CIP) of stoma reversal at 1 and 3 years was calculated, treating death as a competing risk. Factors predictive of stoma reversal were explored using Cox regression analysis. Results: Of 6859 patients included, 35·7, 41·9 and 22·4 per cent respectively had a RRR with a diverting stoma, RRR without a stoma, and Hartmann's procedure with an end-colostomy. In patients with a diverting stoma, the CIP of stoma reversal was 70·3 (95 per cent c.i. 68·4 to 72·1) per cent after 1 year, and 74·3 (72·5 to 76·0) per cent after 3 years. Neoadjuvant treatment (hazard ratio (HR) 0·75, 95 per cent c.i. 0·66 to 0·85), blood loss greater than 300 ml (HR 0·86, 0·76 to 0·97), anastomotic leak (HR 0·41, 0·33 to 0·50), T3 category (HR 0·63, 0·47 to 0·83), T4 category (HR 0·62, 0·42 to 0·90) and UICC stage IV (HR 0·57, 0·41 to 0·80) were possible predictors of delayed stoma reversal. Conclusion: In one-quarter of the patients the diverting stoma had not been reversed 3 years after the intended RRR procedure. Graphical Abstract: In this Danish population-based cohort study, the stoma reversal rate during 3 years of follow-up was estimated among patients undergoing intended restorative rectal cancer resection, and characteristics predictive of stoma reversal were explored. One-quarter of patients had not had their diverting stoma reversed, and more than one-half of patients with anastomotic leakage still had the stoma after 3 years. Stoma reversal after rectal surgery